Optimalisasi Keterampilan Berbicara Mahasiswa melalui Model Hypnoteaching: Inovasi Pembelajaran Abad 21 - Yeti Heryati; Abdul Kosim; Ani Yanti Ginanjar; Muhammad Fanza Maulana (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Speaking is a fundamental language skill that functions as a tool of communication. Therefore, in language learning, speaking skills require special attention to ensure that learning objectives can be effectively achieved. This study aims to examine the optimization of speaking skills through the hypnoteaching model as an innovative approach to 21st-century learning. The research employed a quantitative method with a Quasi-Experimental Design. The data consisted of students’ speaking skill scores before applying the hypnoteaching model, obtained through a pretest, and after applying the model, obtained through a posttest. The mean score of the pretest was 18.27, while the posttest mean score was 23.86. Based on the paired t-test estimation, the results indicated a significant difference between the pretest and posttest scores. This finding demonstrates that the hypnoteaching model can optimize speaking skills by 56%. Considering these results, it is recommended that the hypnoteaching model be implemented as one of the effective teaching models for developing speaking skills.